REVIEW of official opponent of candidate’s thesis by A.S. Shuiskiy “Terrorist acts counteraction by criminal-legal norms with double prevention”, speciality 12.00.08 – Criminal Law and Criminology; Criminal-executive law - P. V. Agapov (Russian Journal of Economics and Law)
The review analyzes strengths and weaknesses of thesis by A.S. Shuiskiy. Topicality and novelty is stressed, as well as practical value of the research.